1990
DOI: 10.1107/s0108767389010457
|View full text |Cite
|
Sign up to set email alerts
|

Diffraction by a randomly distorted crystal. I. The case of short-range order

Abstract: Kato's statistical theory of diffraction [Kato (1980). Acta Cryst. A36, 763-769, 770-778] is reformulated in a self-consistent manner. The local displacement field u(r) occurs through the phase factor φ(r) = exp [2πi h . u(r)]. The present paper is concerned with the limiting case where (φ~(r)) = E = 0: this corresponds to the situation where only secondary extinction is present. There are two correlation lengths in the problem, the first one τ for the phase factor φ, the second one Γ for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Because the experimental data are corrected for absorption, the integrated reflecting power is given for the case of zero absorption. Later, Becker & A1 Haddad (1989bHaddad ( , 1990 Rcoh -t-…”
Section: Results Of Statistical Dynamical Theorymentioning
confidence: 99%
See 3 more Smart Citations
“…Because the experimental data are corrected for absorption, the integrated reflecting power is given for the case of zero absorption. Later, Becker & A1 Haddad (1989bHaddad ( , 1990 Rcoh -t-…”
Section: Results Of Statistical Dynamical Theorymentioning
confidence: 99%
“…Becker & A1 Haddad (1989bHaddad ( , 1990) revised Kato's original approach to statistical dynamical theory and showed that the correlation length F for the wavefield amplitudes is variable within the sample and that it fluctuates around a value of the order of the short-range-correlation length ~-, rather than being constant and of the order of the extinction length A, as proposed with some reservation by Kato (1980a). The expression i~B&A • -=it given by Becker & A1 Haddad (1989b [~e -( T/ tze-t-1/ tz2) exp (-tzeT),…”
Section: E=exp[-(2"rr2/3)h2(u2)]mentioning
confidence: 99%
See 2 more Smart Citations
“…Kato (1991) has recently presented a new discussion of the foundations of the statistical diffraction theory using wave equations that are more general than the Takagi-Taupin equations. The present paper is strictly related to the formulation of Kato (1980a, b), including the modifications introduced by Al Haddad & Becker (1988), by Becket & A1 Haddad (1989Haddad ( , 1990 and by Guigay (1989):. In this formulation the coherent waves have the simple form given in (13), which is expected to be a good approximation in the region around the middle of the Borrmann fan.…”
Section: The General Case E #mentioning
confidence: 99%